Pengaruh Gaya Kepemimpinan dan Motivasi Kerja terhadap Kinerja Karyawan Grand Hawaii Hotel Pekanbaru - David Opel Alexander; Rozi Maulana (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to determine the effect of leadership style and work motivation on employee performance at the Grand Hawaii Hotel Pekanbaru. The research method used in this study uses multiple linear regression analysis and the sampling technique uses saturated sampling with a sample size of 60 respondents. The results of the validity and reliability tests show that the data obtained from the results of the study indicate that all items of the variable statements are declared valid and reliable. The results of the partial hypothesis test (t test) for the leadership style variable (X1) are t count 4.206 and t table 2.002, meaning t count> t table with probability Sig. (0.000) <0.05, and the work motivation variable (X2) is t count 3.035> t table 2.002 with Sig. (0.004) <0.05, then H0 is rejected and H1 and H2 are accepted. And the results of the simultaneous test (F test) the F count value (14.993)> F table (3.16) with Sig. (0.000) < 0.05, then H0 is rejected and H3 is accepted. This means that partially and simultaneously the variables of leadership style (X1) and work motivation (X2) have an effect on employee performance (Y) at the Grand Hawaii Hotel Pekanbaru. And the Determination Test (R2) shows that leadership style and work motivation will have a positive and very strong effect of 0.345 (34.5%) on employee performance while the remaining 0.655 (65.5%) is influenced by other variables not examined in this study.